The road user behaviour of school students in Belgium - Sullman, Mark J. M.; Thomas, Abigail; Stephens, Amanda N. (Elsevier Science B.V., Amsterdam., 2012)
The present study aimed to investigate both the on road behaviour of Belgian school students and the validity of the Adolescent Road User Behaviour Questionnaire (ARBQ) in a sample of students attending school in Belgium. In total, 294 adolescents completed the ARBQ along with measures of their selfreported accident involvement and sensation seeking behaviour. Conﬁrmatory Factor Analysis supported the original factor structure of: "unsafe road crossing", "playing on the road" and "planned protective behaviour" for the 21-item version of the questionnaire, but not for the full scale. Males were found to engage more often in unsafe crossing behaviour and playing on the roads. There were also age differences, with unsafe road crossing increasing with age and engagement in planned protective behaviours improving with age. Those who reported being involved in an accident also reported more frequent engagement in unsafe crossing, playing on the roads, thrill seeking behaviour and lower levels of behaviour inhibition. Therefore, this study conﬁrms that the ARBQ is a useful tool for investigating safety-related behaviours that contribute to accident involvement.
Keywords: Adolescents Behaviour Pedestrians ARBQ Road safety